Dynamic Immune Landscape and VZV-Specific T Cell Responses in Patients With Herpes Zoster and Postherpetic Neuralgia - Peng, Qiao; Guo, Xuejiao; Luo, Yang; Wang, Guocan; Zhong, Lingyu; Zhu, Jiamin; Li, Yunze; Zeng, Xun; Feng, Zhiying (Frontiers in Immunology, 2022)
Objectives Varicella-zoster virus (VZV) can induce herpes zoster (HZ) and postherpetic neuralgia (PHN). Immune cells play an important role in regulating HZ and PHN pathogenesis, but the dynamic immune profiles and molecular mechanisms remain unclear. This study aimed to screen dynamic immune signatures during HZ progression and elucidate the mechanism of VZV-specific T cells in PHN. Methods We used cytometry by time-of-flight (CyTOF) to analyze peripheral blood mononuclear cells (PBMC) samples from 45 patients with HZ and eight age-sex-matched healthy controls, eight PHN samples and seven non-PHN samples. Correlations between the immune subsets and clinical pain-related scores were performed. Further, the characteristics of VZV-specific T cells between PHN and non-PHN patients were evaluated by VZV peptide pools stimulation. The expression level of cytokines, including granzyme B, interleukin (IL)-2, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α was performed via cytometric bead array. Finally, we analyzed the alteration of Ca2+ signals in dorsal root ganglion (DRG)-derived cells after TNF-α stimulation. Results We investigated the dynamic characteristics of the immune landscape of peripheral blood samples of patients with HZ and PHN, and depicted two major dynamic signatures in NK, CD4+ and CD8+ T subsets in patients with HZ, which closely correlated with clinical pain-related scores. The frequency of PD-1+CD4+ T cells, VZV-specific PD-1+CD4+ T cells, and the amount of TNF-α produced by VZV-specific T cells were higher in patients with PHN than without PHN. Furthermore, we showed that TNF-α could induce calcium influx in DRG-derived cells in a dose-dependent manner. Conclusions Our results profiled the dynamic signatures of immune cells in patients with HZ and highlighted the important role of VZV-specific T cells in the pathogenesis of PHN.